2014
DOI: 10.1063/1.4876036
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of a long alkyl chain protic ionic liquid and water

Abstract: A combined experimental/theoretical approach has been used to investigate the role of water in modifying the microscopic interactions characterizing the optical response of 1-butyl-ammonium nitrate (BAN) water solutions. Raman spectra, dominated by the signal from the protic ionic liquid, were collected as a function of the water content, and the corresponding spatial organization of the ionic couples, as well as their local arrangement with water molecules, was studied exploiting classical molecular dynamics … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 41 publications
(40 reference statements)
3
31
1
Order By: Relevance
“…A similar interaction pattern was also concluded for the ionic liquid [emim][OMs] 39. Other ILs for which water has been found to preferably interact with the anion include 1‐butylammonium nitrate [BAN] 45, 1‐butyl‐3‐methylimidazolium chloride [bmim][Cl] 46, as well as 1‐butyl‐3‐methylimidazolium tetrafluoroborate [bmim][BF 4 ] and 1‐butyl‐3‐methylimidazolium hexafluorophosphate [bmim][PF 6 ] 26. In this context it is important to recall our recent results on protic imidazolium based ILs, for which water is likely to coordinate also with the protic cation, and especially so when the anion is bulky and strongly charge‐delocalized as in the case of TFSI 17.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…A similar interaction pattern was also concluded for the ionic liquid [emim][OMs] 39. Other ILs for which water has been found to preferably interact with the anion include 1‐butylammonium nitrate [BAN] 45, 1‐butyl‐3‐methylimidazolium chloride [bmim][Cl] 46, as well as 1‐butyl‐3‐methylimidazolium tetrafluoroborate [bmim][BF 4 ] and 1‐butyl‐3‐methylimidazolium hexafluorophosphate [bmim][PF 6 ] 26. In this context it is important to recall our recent results on protic imidazolium based ILs, for which water is likely to coordinate also with the protic cation, and especially so when the anion is bulky and strongly charge‐delocalized as in the case of TFSI 17.…”
Section: Resultssupporting
confidence: 64%
“…In PILs the interactions established between water molecules and the cation/anion pair have mainly a H‐bonding character 14, 25, 41–43. The nature of these interactions can be probed by 1 H chemical shifts in NMR spectra, and frequency shifts in Raman and infrared spectra in the spectral regions where O–H and N–H stretching modes can be observed 44–48. Upon addition of water, the chemical shifts of the hydrogen atoms belonging to the methyl groups of the cation and the anion do not change significantly, but the chemical shift of hydrogen atoms sitting on water moves down‐field while that of the NH protons moves up‐field, see Figure 4.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the absorbed water results in a decrease in the viscosity, an increase in the conductivity, and a change in the interaction between the cations and anions of the ILs . The presence of water also remarkably affects the surface structure of ILs, such as the number and orientation of ions at the surface, which further change the surface tension of the ILs . However, it was reported that the presence of water in ILs can promote the diffusion of redox species and increase the corrosion rate of alloys .…”
Section: Introductionmentioning
confidence: 99%
“…[28,29] Summarizing, the analysis of both reciprocal space (QI(Q)M(Q)) and distance space (Diff(r)) functions is used to compare X-Ray experimental data and simulations. [38,40] [38,40] …”
Section: Qiðqþmðqþ R Sinðqþ Dq ð4þmentioning
confidence: 99%